Ensino de Inglês para uma Educação Antirracista: desafios e possibilidades - SOUZA, Kamila Mayara Sampaio (Universidade Federal do Oeste do Pará, 2024)
Considering the importance of the Law 10.639/2003, which establishes requirements for the teaching of Afro-Brazilian history and culture in schools, this research aimed to understand how ethnic-racial relations and Afro-Brazilian history are discussed in English classes. In this regard, an online questionnaire was applied to English teachers, with the objective of verifying presence or absence of ethnic-racial relations and Afro- Brazilian history in English classes and identify how these discussions are happening in schools. And also, a bibliographic research was carried out to contributed and updating theoretical fundamentals of this research and understand, through works previously published, what is said about the inclusion of ethnic-racial relations in English classes. Questionnaires were applied to 8 english teachers, and there was greater participation of teachers from private schools, between the age of 22-51, 75% (6) of the teachers said they don’t include ethnic-racial and Afro-Brazilian history relations in English classes, however, 7 of the teachers consider it important to include thnic-racial and Afro- Brazilian history relations in English classes. Regarding teacher education, 7 of the teachers consider that they had contact with ethnic-racial and Afro-Brazilian history during their graduation period, but only two teachers said they felt confident in using content related to ethnic-racial relations, Afro-Brazilian history and culture, when they are teaching English in their classes. Regarding English teaching materials, 62,5% (5) of the teacher answered that ethnic-racial relations and Afro-Brazilian history and culture are not included in the english teaching materials. Data show that despite laws and prescriptions about the inclusion of ethnic-racial relations and Afro-Brazilian history and culture in English classes, there is lacking or insignificant inclusion of this discussion in english classes.